2021
DOI: 10.1007/s00439-021-02313-z
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic truncating variants in CFAP206 cause male infertility in human and mouse

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Second, the sample size of the training cohort was relatively limited, and the external validation was not performed due to the difficulty to collect additional samples. Further studies are needed to accomplish the validation of the predictive model under a systems-level through integrating genomic and clinical information 45 48 , and explore the potential causal effects of these risk factors associated with postoperative hemorrhage under a Mendelian randomization framework 49 – 51 . As the LPD procedures were recommended by the Study Group of Pancreatic Surgery in the Chinese Society of Surgery of Chinese Medical Association 52 , our predictive model can be used only in patients who underwent LPD in the same surgical manner.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the sample size of the training cohort was relatively limited, and the external validation was not performed due to the difficulty to collect additional samples. Further studies are needed to accomplish the validation of the predictive model under a systems-level through integrating genomic and clinical information 45 48 , and explore the potential causal effects of these risk factors associated with postoperative hemorrhage under a Mendelian randomization framework 49 – 51 . As the LPD procedures were recommended by the Study Group of Pancreatic Surgery in the Chinese Society of Surgery of Chinese Medical Association 52 , our predictive model can be used only in patients who underwent LPD in the same surgical manner.…”
Section: Discussionmentioning
confidence: 99%
“…RS1 is adjacent to the base of the inner dynein arm, while RS2 and RS3are respectively attached to the front and back of the nexin–dynein regulatory complex (N-DRC) and the calmodulin- and spoke-associated complex (CSC) ( Zhu et al, 2017 ). Defects of several genes that encode CSC components have been reported to be related to MMAF, including CFAP61 ( Ma A. et al, 2021 ; Liu M. et al, 2021 ; Hu et al, 2022 ), CFAP91 ( Martinez et al, 2020 ), CFAP206 ( Shen et al, 2021 ) and CFAP251 ( Auguste et al, 2018 ; Kherraf et al, 2018 ; Li W. et al, 2019 ; Wang J. et al, 2021 ). Early in 2007, Dymek and Smith conducted immunoprecipitation experiments using anti-CaM antibodies and found that the CSC is comprised of three polypeptides, namely, CaM-IP2, CaM-IP3 and CaM-IP4, which are also termed as CFAP61, CFAP91 and CFAP251, respectively ( Dymek and Smith, 2007 ).…”
Section: Pathogenic Genes and Their Function Inspermatogenesismentioning
confidence: 99%
“…Interestingly, in humans, mutations in genes orthologous to SPEF2A (SPEF2) and CFAP69 turned out to cause MMAF and very rarely PCD (until now, only mutations in SPEF2 were connected to PCD) [190][191][192][193][194][195]. Among other MMAF-causative genes [196,197] studied in Tetrahymena are, as mentioned before, CFAP43 and CFAP44 [127,[198][199][200][201][202], the CSC subunits CFAP61 [203,204] and CFAP251 [204,205], and CFAP206, which forms a part of the RS2 base [126,196].…”
Section: Ciliate: Tetrahymena and Parameciummentioning
confidence: 99%